MODERN METHODS OF PSYCHOTHERAPY IN MENTAL HEALTH PRESERVATION - Raimqulov Rivoj Sobir oʻgʻli (Sciental Journals Publishing, 2025)
This article analyzes the role and relevance of contemporary psychotherapy methods in mental health preservation. Specifically, the theoretical foundations and clinical applications of methods such as cognitive-behavioral therapy, psychoanalytic approaches, psychosomatic medicine, motivational intervention, and family psychotherapy are highlighted. Based on various literature sources, mental states, interpersonal relationships, unconscious processes, and psychophysiological connections are deeply analyzed. The research demonstrates the necessity of integrating psychotherapy methods that take into account individual, social, and emotional factors in strengthening mental health.
Keywords: Psychotherapy, mental health, cognitive-behavioral therapy, psychoanalysis, motivational approach, family therapy, psychosomatic, interpersonal relationships